Devices for Understanding Territory to Rethink Relations Between City and Highland in Alpine Metropolitan Areas - Emmanuel Roux (Revue de Géographie Alpine)
This paper proposes to show how territorial cognitive devices, in their capacity as patterns of representations and expressions of contemporary problems, are indicative of the rationales underpinning the formation of ‘Alpine metropolitan areas’ and shifting relations between city and highland. Drawing on analysis of a corpus of territorial diagnosis studies and interviews with policy-makers and technicians belonging to a metropolitan council in the French Alps, we show that cognitive devices primarily express the rationales of juxtaposition and interweaving of urban and mountainous issues. They also express the prospects and pitfalls for integrating mountain municipalities in a metropolitan area. Lastly they reveal the emergence of devices for adaptation and mediation to ease the formation of metropolitan areas in the Alps with reciprocal relationships between city and highland.